A survey on campus sustainability assessment framework (CSAF) in Malaysia - Saadatian .O; Salleh .E; Tahir .O.M; Haw .L.C; Sopian .K (Penerbit UKM, 2011)
Campus Sustainability Assessment Framework (CSAF) is a famous Canadian tool, which assess the level of sustainability of universities. However, the compatibility of this tool for other countries such as Malaysia has always been a matter of a question. This study has conducted a questionnaire survey on community indicators of CSAF at four Malaysia research universities namely UM, UPM, UKM and USM. The result indicates that four categories of 1. Involvement and cohesion, 2. Diversity, and 3. Services and 4. Programmes serve as the main rubrics of sustainability in terms of community.